Where Did FinTechs Come From, and Where Do They Go? The Transformation of the Financial Industry in Germany After Digitalization - Brandl, Barbara; Hornuf, Lars (Frontiers in Artificial Intelligence, 2020)
The digitalization of financial services opened a window for new players in the financial industry. These start-ups take on tasks and functions previously reserved for banks, such as lending, payments, or investment. In this article, we trace the transformation of the industry after digitalization. By using data on FinTech formations in Germany, we provide first evidence that entrepreneurial dynamics in the FinTech sector are not so much driven by technology as by the educational and business background of the founders. Furthermore, we investigate the reactions of traditional banks to the emergence of these start-ups. In contrast with other emerging industries such as biotechnology, a network analysis shows that FinTechs have mostly engaged in strategic partnerships and only a few banks have acquired or obtained a financial interest in a FinTech. We explain the restraint of traditional banks to fully endorse the new possibilities of digitalized financial services with the characteristics of the technology itself and with the postponed fundamental decisions of banks to modernize their IT infrastructure.